8-order low-power digital FIR filter design - Shi, Yucen (Nanyang Technological University, 2022)
In recent years, the development of portable devices such as biomedical devices, Internet of things, wearable devices and mobile phones is faster and faster, with more and more powerful processing functions and faster running speed, which inevitably brings huge power consumption. Moreover, with the continuous reduction of process linewidth and the continuous increase of chip power density, however, there has been no breakthrough in battery technology. Therefore, the battery life ability has become an important reason restricting the development of these portable devices. Therefore, the development of low-power technology is imperative. In the direction of digital signal processing, digital filters are widely used because of their various advantages. Among them, FIR filters are particularly favored because of their linear phase characteristics, and are often used in medical devices such as hearing aids. Therefore, the study of FIR filter has a very broad application prospect. Based on the traditional digital FIR filter, this dissertation optimizes and improves its architecture, and finally designs an 8-order low-power digital FIR filter.